The Value of Trainee Networks in Pediatric Surgical Research - Skerritt, Clare; Hall, Nigel J. (European Journal of Pediatric Surgery, 2015)
In 2007, the first trainee-led surgical research network was founded in the United Kingdom (UK). The West Midlands Research Collaborative was started by a group of enthusiastic adult surgical trainees who saw the benefits of altruistic collaboration to generate high quality, multicenter research. Seeing the success of their research projects, including randomized controlled trials, trainees in other regions and specialties were spurred on to founding their own research collaboratives. The Pediatric Surgical Trainee Research Network was started in 2011 by a group of UK trainees with the aim to promote, facilitate, and encourage trainee-led research in pediatric surgery. This article summarizes the history and evolution of the trainee collaborative surgical research. It examines the challenges which multicenter research entails and the steps the collaboratives have taken to overcome them. We describe some of the projects which have been successfully completed and the benefits that the trainee networks have for patients and surgeons alike.
Keywords: surgical research; research network; clinical research; pediatric surgery